Shell shape-habitat correlations in extant turtles: A global-scale analysis - Fanrong Xiao; Zhixue Lin; Jichao Wang; Hai-Tao Shi (Global Ecology and Conservation, 2023)
Animal morphological structure can influence behaviour and interaction with the environment. Owing to their wide range of habitats, from aquatic to terrestrial, and their variation in shell shapes, turtles are highly suitable for ecomorphological studies. However, previous studied have encountered several limitations, including small sample sizes, simplified habitat classification, and no consideration of sexual dimorphism, that may prevent the identification of the ecological mechanisms responsible for divergent morphologies of turtles on a global scale. In this study, we collected the carapace length (CL), carapace width (CW), and carapace height (CH), as an indicators of body size, from 6664 adult individuals of 115 species, 61 genera, and 11 families and calculated the ratio between the CH and CW to delineate shell shape. These turtle species were divided into four habitat types (marine, freshwater, mainland, and island) and eight subtypes (freshwater: large lentic, large lotic, small lentic, small lotic, all water bodies; mainland: desert, flatland, highland) to better understand the ecomorphological alteration of their shell shape. The results of the linear regression showed that shell shape became flat with increasing body size in aquatic turtles, whereas the opposite trend was observed for male mainland tortoises. According to the results of the general linear model, there was a gradual increase in the domed shape of turtle shells from sea to freshwater habitats, from freshwater to mainland terrestrial habitats, and from mainland to island terrestrial habitats. There were no significant differences between the shell shape and habitat subtype for freshwater turtles and mainland tortoises. To the best of our knowledge, this study represents the first investigation into the variation pattern of shell shape in turtles living in habitats ranging from marine to island and its relationship to body size. The study results suggest that conservation strategies for turtles should consider both their shell shape and habitat characteristics.